2022
DOI: 10.3393/ac.2020.01032.0147
|View full text |Cite
|
Sign up to set email alerts
|

Longer prolapsed rectum length increases recurrence risk after Delorme’s procedure

Abstract: Risk factors for recurrence of rectal prolapse after surgery remain unclear. Delorme's procedure is often selected for relatively small-sized rectal prolapse, but there are few reports discussing the association between prolapsed rectum length and prolapse recurrence after Delorme's procedure. We hypothesized that patients with longer rectal prolapses are at a higher risk of recurrence after Delorme's procedure. Methods: The study population comprised patients with rectal prolapse who underwent Delorme's proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…The Delorme and Altemeier procedure, classic transperineal procedure, are easy to perform, minimize injury, and require low patient tolerance for surgery, but have a high rate of postoperative recurrence [6]. A recent study shown that the recurrence rate of the Delorme procedure was as high as 25%, and correlated with the length of the prolapse [7]. A retrospective study in Europe found that recurrence and major postoperative complications (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The Delorme and Altemeier procedure, classic transperineal procedure, are easy to perform, minimize injury, and require low patient tolerance for surgery, but have a high rate of postoperative recurrence [6]. A recent study shown that the recurrence rate of the Delorme procedure was as high as 25%, and correlated with the length of the prolapse [7]. A retrospective study in Europe found that recurrence and major postoperative complications (e.g.…”
Section: Discussionmentioning
confidence: 99%